A comparison of patient-reported quality between inpatient services for mental and physical health: A tertiary-hospital-based survey in China - Zhou, Wei; Xiao, Shuiyuan; Xie, Guanqing; Ouyang, Feiyun; Luo, Bihua (Frontiers in Psychiatry, 2023)
Background It is widely acknowledged that quality of mental health services is routinely worse than physical health services across countries. However, studies separately investigating mental health services often report high-level satisfaction, even comparing with physical health services. Therefore, this study aimed to compare patient-reported quality between inpatient services for mental and physical health in China. Methods An inpatient survey was conducted among service users of mental and physical health services. Patient-reported quality was measured by the responsiveness performance questionnaire after patient discharge and based on patients' multiple experiences of hospitalization in the past 3 years. Chi-square tests were performed to compare the two patient groups' ratings on inpatient services for mental and physical health, and multivariate logistic regression was performed to adjust covariates in the group comparison. Results Inpatient services for mental health were rated better than those for physical health on “treating with respect” (AOR = 3.083, 95% CI = 1.102–8.629) and “choosing a healthcare provider” (AOR = 2.441, 95% CI = 1.263–4.717). However, mental health services had poorer ratings on “asking patient's opinions” (AOR = 0.485, 95% CI = 0.259–0.910). For other responsiveness items, no significant difference was detected between the two types of inpatient services. Conclusion Mental health inpatient services provided by China's tertiary hospitals could perform as well as physical health inpatient services in most aspects and even better perform regarding dignity and choice of healthcare providers. However, neglecting patients' voices is more severe in inpatient services for mental health.